In Need of a Roof: Pandemic and Housing Vulnerability - Kusum Mundra; Ruth Uwaifo Oyelere (Institute of Labor Economics (IZA), 2022)
Housing is a basic need and is intricately connected to a household's health and wellness. The current pandemic has exposed the housing vulnerability for certain subgroups of the population and further jeopardized these household's health and stability. Using the Household Pulse Survey launched by the US Census Bureau since April 2020, we examine the correlates of housing vulnerability during the pandemic. We explore both subjective and objective measures of vulnerability. In addition, we explore heterogeneity in the evolution of housing vulnerability along demographic characteristics such as ethnicity and housing type (renter vs owner) during the pandemic. Our results suggest that individuals perception on their housing vulnerability in the immediate future is on average higher than the objective evaluation of their current vulnerability. In addition, not being employed, lower levels of education and household size all increase home vulnerability. We also find significant heterogeneity across race in the evolution of vulnerability during the pandemic (2000-2022) with a "chilling effect" on Asians.
Keywords: R2; R3; J10; I31; 330; renter; homeowner; housing vulnerability; pandemic; ethnicity; Asian; COVID-19